2018
DOI: 10.1103/physrevb.97.134427
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties of Co-doped Nb clusters

Abstract: From magnetic deflection experiments on isolated Co doped Nb clusters we made the interesting observation of some clusters being magnetic, while others appear to be non-magnetic. There are in principle two explanations for this behavior. Either the local moment at the Co site is completely quenched or it is screened by the delocalized electrons of the cluster, i.e. the Kondo effect. In order to reveal the physical origin, we conducted a combined theoretical and experimental investigation. First, we established… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…The original Stern-Gerlach experiment was designed to determine the magnetic moment of isolated silver atoms; 22 later various other isolated atoms, 23 several molecules with a nonzero spin S [24][25][26][27][28][29][30][31][32][33][34] and metallic and bi-metallic clusters [35][36][37][38][39][40][41][42][43][44][45][46][47] were investigated with Stern-Gerlach setups (except for ref. 46).…”
Section: Introductionmentioning
confidence: 99%
“…The original Stern-Gerlach experiment was designed to determine the magnetic moment of isolated silver atoms; 22 later various other isolated atoms, 23 several molecules with a nonzero spin S [24][25][26][27][28][29][30][31][32][33][34] and metallic and bi-metallic clusters [35][36][37][38][39][40][41][42][43][44][45][46][47] were investigated with Stern-Gerlach setups (except for ref. 46).…”
Section: Introductionmentioning
confidence: 99%
“…This is confirmed by a comparison of the vibrational spectra obtained within DFT and experiments. 5 Furthermore, in Ref. 12 it is correctly predicted within DFT that Nb 7 Co should be non-magnetic.…”
Section: Nbcomentioning
confidence: 93%
“…[1][2][3][4] For example, in a recent work on Nb x Co clusters it is demonstrated that Nb 5 Co and Nb 7 Co are non-magnetic, while Nb 4 Co and Nb 6 Co are strongly magnetic. 5 The physical origin of this behavior can be traced back to the drastic change of the electronic structure as a function of cluster size.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations